Analysis to Calculate Mortality and Adverse Outcomes Among Health Workers and General Population with Covid-19 - Raisa Naz, Rubina Anjum, Syed Abdul Rauf Shah, Amanat Ali, Imran Mehboob Baig, Abdul Azeem (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The primary objective of this research is to evaluate the mortality rates from coronavirus infection among healthcare workers against those in the general population. Study Design: Comparative/Retrospective study Place and Duration: Medical Unit Ward and Emergency Department, Ayub Medical College Abbottabad, July, 2021 to Dec, 2021. Methods: 190 coronavirus-infected patients of both sexes participated. 20-65-year-old patients were enrolled. All cases gave written consent for age, sex, BMI, socioeconomic status, and domicile. Patients were symptomatic and asymptomatic. Group A had 95 cases of general population and in group B 95 were health workers. In coronavirus ward patients were observed for recovery. Outcomes were ICU hospitalization, need of ventilation, and mortality rates were compared. We analyzed data with SPSS 20.0. Results: We found that majority of the patients among both groups were asymptomatic 55 (57.9%) in group A and 59 (62.1%) in group B. Most common comorbidities were HTN, DM and IHD. Use of preventive measures in group A 35 (36.8%) was lower as compared to group B 70 (73.75) with p value <0.003. We found that number of ICU admission 17 (17.9%), ventilation requirement 20 (21.05%) and mortality 13 (13.9%) in group A was significantly higher with p value 0.005 as compared to group B 5 (5.3%), 6 (6.3%) and 3 (3.2%). Conclusion: In this study, we found that the incidence of mortality, admissions to the intensive care unit, and the use of invasive ventilation were all much greater in the general population than they were in the health care professional group. Keywords: Ventilation, General Population, COVID-19, Mortality, ICU, Health workers